Transparency of Financial Reporting According to the S&P500 Indices and its Implications for Accounting Information Risks - Evidence from the Iraq Stock Exchange - Wahhab, Asaad; Al Fattehallah, Mohammed Abd Ali M.A.; Alsujair, Mohammed Hwueish Allawi (Technium Business and Management, 2022)
The current research aims to test and analyze the relationship between the level of transparency of financial reporting and the risks of accounting information for a sample of private commercial banks in the Iraq Stock Exchange. The transparency of financial reporting was assessed using the S&P500 indices, and the level of accounting information risk was evaluated using the S&P500 indices, representing fragmented and reduced risks. Unanswered information within the S&P500 indices' requirements consists of 98 conditions. To achieve the research objectives and test its hypotheses, the applied approach was used to evaluate the research variables in a sample of commercial banks listed on the Iraq Stock Exchange, which amounted to (10) selected banks for the period (2016-2021). In comparison, the inferential statistical method was used to test and analyze the research hypotheses using Excel and SPSS26 programs. The research reached a set of conclusions, the most important of which was the low level of transparency in private commercial banks, especially in the two main categories of (S&P500) indicators: ownership structure and shareholder rights, and the board of directors and management procedures, as both had the largest share of risks, which indicates a high risk of accounting information. The research concluded with several recommendations, the most important of which was working to oblige banks to expand disclosure and work with the mechanisms of S & P500 indicators and apply them annually to follow up on the level of transparency development in them to reduce the risks of accounting information.